The effect of tantalum incorporation on the physical and chemical properties of ternary silicon–calcium–phosphorous mesoporous bioactive glasses. Issue 7 (24th January 2019) - Mendonca, Andrew; Rahman, Md. Saidur; Alhalawani, Adel; Rodriguez, Omar; Gallant, Reid C.; Ni, Heyu; Clarkin, Owen M.; Towler, Mark R.
Abstract: Synthesis and characterization of the first mesoporous bioactive glasses (MBGs) containing tantalum are reported here, along with their potential application as hemostats. Silica MBGs were synthesized using with the molar composition of (80‐x)% Si, 15% Ca, 5% P, and x% Ta. It was found that incorporation of >1 mol % Ta into the MBGs changes their physical and chemical properties. Increasing Ta content from 0 to 10 mol % causes a decrease in the surface area and pore volume of 20 and 35%, respectively. This is due to the increase in nonbridging oxygens and mismatch of thermal expansion coefficient which created discontinuities in the ordered channel structure. However, the effect is not significant on the amount of ions (Si, Ca, P, and Ta) released, from the sample into deionized water, for short durations (<60 min). In a mouse tail‐cut model, a significant decrease in bleeding time (≥50% of average bleeding time) was found for Ta‐MBGs compared to having no treatment, Arista, and MBG without Ta. Further studies are proposed to determine the mechanism of Ta involvement with the hemostatic process. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 2229–2237, 2019.